2010
DOI: 10.1111/j.1439-0442.1975.tb01426.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Protein Level and NH4Cl addition to Diet on Ammonia Detoxication in Rats

Abstract: Summary The effect of the nitrogen content of the diet on ammonia detoxication in rats was studied using 6 diets containing 5, 15 and 70% casein with or without 2% NH4Cl. Evaluation of ammonia detoxication was based on the estimation of the LD50 of intraperitoneally administered NH4Cl, on the levels of ammonia, urea and glucose in blood, and on the arginase, δ‐ornithine transaminase and ornithine transcarbamylase activities in the liver and on ATP + ADP concentration in the liver, kidneys and muscles. Higher d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2010
2010
2010
2010

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 19 publications
1
3
0
Order By: Relevance
“…In the present experiment, the additional determination of the level of a-ketoglutarate in the blood and in the liver of rats did not show significant intergroup differences as regards this metabolite. KULASEK et al (1975) believe that a higher metabolic rate of ornithine to glutamate under the influence of 8-ornithine transaminase does not have to be related to a decreased synthesis of urea; this is also confirmed by the present investigations ( Figs. 2 and 3).…”
Section: Janithinesupporting
confidence: 90%
See 1 more Smart Citation
“…In the present experiment, the additional determination of the level of a-ketoglutarate in the blood and in the liver of rats did not show significant intergroup differences as regards this metabolite. KULASEK et al (1975) believe that a higher metabolic rate of ornithine to glutamate under the influence of 8-ornithine transaminase does not have to be related to a decreased synthesis of urea; this is also confirmed by the present investigations ( Figs. 2 and 3).…”
Section: Janithinesupporting
confidence: 90%
“…However, one may suppose that the maintainance of an increased subtoxic level of ammonia in the organism over a longer period of time considerably increases the effectiveness of the mechanisms participating in its detoxication. The first successful experiments of this kind were investigations on rats conducted by KULASEK et al (1975) who observed that the addition of ammonium chloride to the fodder, under ad libitum feeding conditions, creates a situation in which animals acquire a more effective ammonia detoxication.…”
Section: Introductionmentioning
confidence: 99%
“…In the liver the activities of ornithine aminotransferase (KTO) (2.6.1.13), arginase (3.5.3.1) and ornithine transcarbamylase (OTC) (2.1.3.3) were determined. The technique of these analyses was described in a previous paper (10).…”
Section: Methodsmentioning
confidence: 99%
“…An increase of dietary nitrogen concentration in the form of protein (1, 14) or non-protein nitrogen compounds (NPN) (10,ll) leads after several days to an induction of urea cycle enzymes and other enzymes connected with ammonia detoxication in the liver of experimental animals. It is suggested (10,11) that in the case of NPN diets as well as high protein ones, the organism is loaded with ammonia, in the latter case as a result of intensive amino acid catabolism. SCHLIENGER et al (15) and BAREJ and HARMEYER (2) showed that loading animals with ammonium salts leads to a decrease of immunoreacting insulin (IRI) in the blood.…”
Section: Introductionmentioning
confidence: 99%